Career Adaptability as a Psychological Bridge: Linking Perceived Social Support to Coping Strategies among Working University Students - Abdullah, Sri Muliati; Fauzi, Syahrul Dimas Nur; Kuncoro, Muhammad Wahyu; Kurniawan, Aditya Putra (Indonesian Psychological Research, 2026)
TThis study examined whether career adaptability partially mediates the relationships between perceived social support and coping strategies among working university students. Using a quantitative cross-sectional survey design, data were collected from 247 undergraduate students who had worked part-time or full-time for at least three months. Participants completed the Indonesian versions of the Career Adapt-Abilities Scale-Short Form (CAAS-SF), the Multidimensional Scale of Perceived Social Support (MSPSS), and the Ways of Coping Questionnaire Revised Version. The primary analytical objective was to test the mediation pathways using Partial Least Squares Structural Equation Modeling with bootstrapping. Perceived social support was positively associated with career adaptability, problem-focused coping, and emotion-focused coping. Career adaptability was also positively associated with both coping strategies. The significant indirect effects indicated partial mediation. These findings support a focused explanation of one psychological pathway, that is social support is associated with coping both directly and indirectly through career adaptability. Universities should provide targeted career-adaptability development, peer support, and academic guidance for students balancing work and study.